JUVENILE JUSTICE: ALTERNATIVE COMMUNITY SERVICE WHEN DIVERSION IS NOT ACHIEVED - Fajriyah, Aida Ihsaniati; Airlangga, Rendy (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The effectiveness of basic punishments for children in conflict with the law when diversion is not achieved, particularly regarding community service as an alternative punishment, is the focus of this study. The purpose is to determine the most appropriate form of punishment for children when diversion fails and to assess whether community service is the best option. Using a normative juridical method, the study finds that each basic punishment in Article 71 Paragraph (1) of the Juvenile Criminal Justice System Law has its strengths and weaknesses. A warning is too lenient, guidance outside the institution emphasizes rehabilitation but lacks facilities, supervision allows normal activities but has no deterrent effect, job training is potentially beneficial but often noncompliant, and institutional guidance faces obstacles in fulfilling children's rights. Imprisonment is the least effective because it negatively affects children's psychological and social conditions and should be a last resort. Among all punishment, community service is deemed most ideal as it aligns with corrective, rehabilitative, and restorative principles, keeps children in their environment, and fosters social responsibility and empathy